Racial Disparities in the Enforcement of COVID-19 Public Health Violations - Leal, Wanda (Crime & delinquency, 2025)
To curb the spread of the novel coronavirus, most cities and states implemented COVID-19 public health restrictions that became enforceable offenses. Unfortunately, concerns about unequitable enforcement arose among minority and impoverished communities. The current study uses official data from San Antonio, Texas to investigate the relationship between zip code racial and ethnic composition and income on the enforcement of COVID-19 public health violations. Over 28,000 enforcement activities from March 2020 to March 2021 were analyzed using random effects logistic regression. Results indicate that enforcement activities in zip codes with above average percent Black and above average percent Hispanic were more likely to receive citations, even though citations were issued in less than one percent of all enforcement activities.